Dosage form preference consultation study in children and young adults: paving the way for patient-centred and patient-informed dosage form development. Issue 6 (2nd September 2016) - Alyami, Hamad; Dahmash, Eman; Alyami, Fahad; Dahmash, Dania; Huynh, Chi; Terry, David; Mohammed, Afzal R
Abstract : Objectives: The current study aims to evaluate dosage form preferences in children and young adults together with identifying the key pragmatic dosage form characteristics that would enable appropriate formulation of orally disintegrating tablets (ODTs). Methods: International, multisite, cross-sectional questionnaire of children and young adults aged from 6 to 18 years. Eligibility was based on age, ability to communicate and previous experience in taking medications. The study was carried out at three locations: the UK, Saudi Arabia and Jordan. The questionnaire instrument was designed for participant self-completion under supervision of the study team. Results: 104 questionnaires were completed by the study cohort (n=120, response rate 87%). Results showed that ODTs were the most preferred oral dosage forms (58%) followed by liquids (20%), tablets (12%) and capsules (11%). The preferred colours were pink or white while the preferred size was small (<8 mm) with a round shape. With regard to flavour, strawberry was the most preferred (30.8%), while orange was the least preferred (5.8%). The results also showed that the most important physical characteristics of ODTs were disintegration time followed by taste, size and flavour, respectively. Conclusions: The results of our study support the WHO's claim for a shift of paradigm from liquid towards ODTs dosage forms for drug administration to young children older than 6 years. Data from this study will also equip formulators to prioritise development of key physical/performance attributes within the delivery system.